Notch signaling pathway in the development of imbalanced immune responses in patients with disseminated pulmonary tuberculosis - A. E. Sanina; V. A. Serebryakova; O. I. Urazova; A. A. Gadzhiev (Бюллетень сибирской медицины)
Aim. To determine the role of the Notch signaling pathway in the regulation of Th1 / Th2 lymphocyte balance in patients with disseminated drug-sensitive (DS) and drug-resistant (DR) pulmonary tuberculosis (PT).Materials and methods. Mononuclear leukocytes were isolated from the venous blood of 13 patients with disseminated PT by density gradient centrifugation. The cells were cultured for 72 h in the complete cell culture medium at 5% CO2 and 37 °C. Preliminarily, CFP10 and ESAT6 mycobacterial antigens or γ-secretase inhibitor DAPT (5 μM / l; 10 μM / l) together with CFP10 and ESAT6 antigens were added to the culture medium. Immunophenotyping of Th1 and Th2 lymphocytes was performed by multicolor flow cytometry by determining the expression of CD4 receptor and intracellular transcription factors T-bet and GATA-3.Results. In patients with disseminated DS and DR PT, an increase in the number of Th1 and Th2 lymphocytes was found in intact cultures. Stimulation of cells with mycobacterial antigens CFP10 and ESAT6 resulted in an increase in the number of CD4+T-bet+ and CD4+GATA-3+ cells in all comparison groups. Addition of CFP10 and ESAT6 antigens and DAPT (10 μM / l) to the incubation medium was accompanied by a decrease in the number of Th2 lymphocytes in PT patients in both groups. A rise in the number of Th1 cells was registered only in patients with DS PT. Suppression of the Notch signaling pathway with the γ-secretase inhibitor DAPT (10 μM / l) resulted in an increase in the Th1 / Th2 lymphocyte balance in both DS and DR variants of the disease.Conclusion. The Notch signaling pathway has a modulating effect on the differentiation of the key lymphocyte populations that determine the balance between cell-mediated and humoral immune responses to PT. Suppression of the Notch signaling cascade by the γ-secretase inhibitor DAPT (10 μM / l) in vitro promotes an increase in the Th1 / Th2 ratio in patients with disseminated DS and DR PT. The positive regulatory effect on the Th1 / Th2 lymphocyte balance allows to consider the Notch signaling pathway as a promising potential target in the development of new approaches to the pathogen-specific therapy for PT.